ANALISIS STRATEGI PEMASARAN AIR MINERAL DI DEPOT ISI ULANG AQUALITY CABANG TILAMUTA KABUPATEN BOALEMO - Fibriyanti S. Lakoro; Sukrianto Sukrianto (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study was to determine the marketing strategy of mineral water at the Aquality Refill Depot, Tilamuta Branch, Boalemo Regency. The type of research used is qualitative with a descriptive approach. The data analysis method is used by collecting documents and interviews. Then read, analyze and record the collected data. As well as discussing the problems posed in the research which were analyzed using qualitative techniques. The results of the study explain that the Aquality Refill Depot, Tilamuta Branch, Boalemo Regency must be able to provide and prepare strategy formulations that are able to minimize weaknesses and threats that often arise. In maintaining the product even though competition in the same business must be able to be minimized. With the product strategy such as pricing, distribution and promotion that must be improved, especially in distribution and promotion, which is needed for improvement